Pengaruh Debt to Asset Ratio, Debt to Equity Ratio dan Long Term Debt to Equity Ratio terhadap Return on Equity Ratio pada Industri Property yang Terdaftar Dibursa Efek Indonesia Periode 2013-2017 - Nia Asnita (Universitas Batanghari Jambi, 2019)
The study aims analyze whether debt to asset ratio, debt to equity ratio dan long term debt to equity ratio have a significant or partical effect on the return on equity at property industry on the Indonesia Stock Exchange 2013-2017. This sereach uses quantitative descriptive analysis method qualitative descriptive analysis. The analytical tool of this research is the same as the analytical method. Namely multiple linier regression using log. The result of the study show that simultaneous from this study show the effect of debt to asset rasio, debt to equity ratio and long term debt to equity ratio on the return on equity at industry property which is listed on the Indonesia stock exchange for the preoid 2013-2017. Simultaneously with the number of Fcount 1.687 and Ftable 3.10. it can bee seen that Fcount < Ftable is 1.687 < 3.10. meaning that there is a no signifikan effect on debt to asset ratio, debt to equity ratio and long term debt to equity ratio on the return on equity. Partial influence on debt to asset ratio, debt to equity ratio againt the return on equity at industry property, which is listed on the Indonesia stock exchange for the period 2013-2017. Whit the debt to asset ratio of t 0.462 and 2.08596 tables meants t count < t table, 0.462<2.08596, meaning total debt to asset ratio does not have a positive effect on return on equity. Dbt to equity ratio of t 1.291 and 2.08596 tables meants t coun < t table, 1.291<2.08596, meaning tota debt to equity ratio does not have a positive effect on return on equity, long term debt to equity ratio of t -2.248 and 2.08596 taables meants t count < t table, -2.248<2.08596, meaning total long term debt to equity ratio does not a have positive effect on return on equity the period 2013-2017.